Mapping intrashell variation in Mg/Ca of brachiopods to external growth lines: Mg enrichment corresponds to seasonal growth slowdown - Müller, Tamás; Tomašových, Adam; Correa, Matthias López; Mertz-Kraus, Regina; Mikuš, Tomáš (Chemical Geology, 2022)
Determining secular changes in seawater temperature and Mg/Ca ratio is of high importance in paleooceanographic, paleoenvironmental and paleoecological studies. On the one hand, intra-shell variation in Mg/Ca in brachiopod shells is used to reconstruct historical changes in temperature and in seasonality. On the other hand, intra-shell analyses show a weak relationship between Mg/Ca and δ18O, but a positive correlation between Mg/Ca and Sr/Ca, and an increase of Mg/Ca at growth lines, indicating that Mg/Ca does not simply track seawater temperature alone. Internal growth lines are rarely visible in brachiopod shells, and the relation between growth lines that mark growth slowdown or cessation and Mg/Ca fluctuation is thus not properly understood. Here, using four species of extant brachiopods from the NE Pacific and the SW Pacific, from environments with low seasonality in seawater temperature (<5 °C), and two species of Late Triassic brachiopods (Western Carpathians), we measure intra-shell ontogenetic variation in Mg/Ca, S/Ca and Sr/Ca with laser ablation ICP-MS and electron microprobe. In contrast to previous studies, we map variation in Mg, S, and Sr to external growth lines. We find that, first, zones of Mg/Ca enrichment in the secondary layer form 10–50 μm-thick discrete bands or clusters of micrometric bands that consistently terminate at major external, predominantly annual growth lines that are associated with distinct notches that correspond to mantle retractions in most species. These bands generate distinct peaks in Mg/Ca that stand above low, more uniformly distributed background Mg/Ca values along laser-ablation and microprobe transects. The magnitude of Mg/Ca in these bands is comparable to Mg/Ca in the primary layer, exceeding background values of Mg/Ca in the secondary layer by 5–20 mmol/mol (by a factor of two to five). Second, Mg enrichment in discrete bands is closely associated with an increase in S concentrations in the secondary layer. Therefore, even when Mg and S uptake is expected to be highest under fast precipitation rate, these empirical observations show that Mg and S enrichment occur in the zones that were precipitated at times of a significant growth reduction (e.g., in cold-temperate brachiopods studied here during winters when primary productivity is low). The mechanisms for this paradox are unclear but can be related to uptake of Mg by amorphous calcium carbonate (ACC) to delay the transformation of ACC to calcite during the formation of growth lines. Therefore, intra-shell variation in Mg/Ca in brachiopods with major growth lines is primarily determined by seasonal decline or cessation in shell growth and not by seasonal changes in seawater temperature.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Biomineralization; Brachiopoda; Growth rate; Mg/Ca ratio; S/Ca ratio; Seasonality; Sr/Ca ratio